Identification of Differences in the Seasonality of the Developer and Individual Housing Market as a Basis for Its Sustainable Development - Paweł Frącz; Ireneusz Dąbrowski; Daria Wotzka; Dariusz Zmarzły; Łukasz Mach (Buildings, 2023)
This article identifies seasonality profiles for three stages of housing construction. The profiles were determined as average monthly values obtained for permits issued for the construction of new apartments, for apartments whose construction has begun, and for apartments put into operation. The research process showed that there are differences in seasonality profiles between investments carried out by individual investors and those who build apartments for sale or rent. The research clearly showed that the development of reports and analyses for the housing market should include a breakdown of the market for the activities of individual developers as well as those operating as investments. Unfortunately, at present, reports on the real estate market are developed in total terms, which significantly reduces their utilitarian application. Taking into account the recommendations of the research will allow for sustainable development of the housing market in such a way that the market will strengthen its resilience to the occurrence of cyclical fluctuations, among other things.